2020
DOI: 10.3390/ijms21093404
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Cardiovascular Diseases with hiPSC-Derived Cardiomyocytes in 2D and 3D Cultures

Abstract: In the last decade, the generation of cardiac disease models based on human-induced pluripotent stem cells (hiPSCs) has become of common use, providing new opportunities to overcome the lack of appropriate cardiac models. Although much progress has been made toward the generation of hiPSC-derived cardiomyocytes (hiPS-CMs), several lines of evidence indicate that two-dimensional (2D) cell culturing presents significant limitations, including hiPS-CMs immaturity and the absence of interaction between different c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 180 publications
(237 reference statements)
0
53
0
1
Order By: Relevance
“…Our study focuses on cardiomyocytes, a cell type that can be differentiated from hiPSCs and undergoes a process of differenti-ation and maturation over extended time in culture or as engineered tissue, under carefully controlled conditions (Lundy et al, 2013;Ronaldson-Bouchard et al, 2018;Sacchetto et al, 2020). We provide a rigorously quality-controlled and standardized approach to quantify transcript abundance, local and global subcellular organization, and relationships between quantitative observations in tens of thousands of single cells (Figures 1A and 4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study focuses on cardiomyocytes, a cell type that can be differentiated from hiPSCs and undergoes a process of differenti-ation and maturation over extended time in culture or as engineered tissue, under carefully controlled conditions (Lundy et al, 2013;Ronaldson-Bouchard et al, 2018;Sacchetto et al, 2020). We provide a rigorously quality-controlled and standardized approach to quantify transcript abundance, local and global subcellular organization, and relationships between quantitative observations in tens of thousands of single cells (Figures 1A and 4).…”
Section: Discussionmentioning
confidence: 99%
“…To do this, we performed RNA FISH for 16 gene transcripts as multiplexed pairs in 11,135 alpha-actinin-2-mEGFP expressing cardiomyocytes at D18 and D32 (Figures S5A-S5C; Table S3). Five of these genes were chosen because of their association with known sarcomere biology at a structural, regulatory, or functional level and included MYL7, ATP2A2, TCAP, NKX2.5, and BAG3 (Judge et al, 2017;Kasahara et al, 2003;Kubalak et al, 1994;MacLennan et al, 1985;Mason et al, 1999;Sacchetto et al, 2020). The remaining 11 genes were chosen based on results in a complementary transcriptomic study (Grancharova et al, 2021), where groups of genes were identified for their ability to correctly assign cardiomyocytes to a selected time point, which included MYH7, MYH6, COL2A1, H19, VCAN, CNTN5, MEF2C, PLN, PRSS35, BMPER, and housekeeping gene HPRT1 (Bargehr et al, 2019;Bertero et al, 2019;Friedman et al, 2018;Palpant et al, 2017) (Figures 6B-6E and S5A-S5C).…”
Section: Quantifying the Relationship Between Transcript Abundance And Structural Organization In Single Cellsmentioning
confidence: 99%
“…For instance, pluripotent stem cells have enabled the generation of patient derived cells harboring genetic predispositions to certain cardiac diseases for in vitro applications. 31 Moreover, inspired by pathophysiological mechanisms of acquired diseases, healthy cardiac tissues under mechanical or chemical conditioning are used to induce a disease-like phenotype. 32 Combined with genetically altered CMs, they can become a powerful tool to understand environmental triggers of patients with specific genetic dispositions to cardiac diseases.…”
Section: Disease Modelsmentioning
confidence: 99%
“…hiPSC‐CMs have become the most important cell source for cardiac disease modeling, cardiotoxicity studies, and cardiac regenerative therapies. [ 55,56 ] Hence, the direct availability of large numbers of hiPSC‐CMs has become crucial and extensive research regarding their cryopreservation has been conducted. Currently, the two most used cryopreservation solutions for hiPSC‐CM storage are CryoStor CS10 and FBS supplemented with CPAs, most frequently DMSO.…”
Section: Cryopreservation Of Cardiac Samplesmentioning
confidence: 99%